TRAINING ON PROPOSAL MAKING OF TRADITIONAL RANGE FESTIVAL SPONSORS IN DUKUH DEMPING, ANGGRASMANIS, JENAWI, KARANGANYAR - Dian Indriana Hapsari; Guruh Taufan Hariyadi; Juli Ratnawati; Imang Dapit Pamungkas (Bajang Institute, 2022)
Advances in science, technology and science are developing so rapidly. But unfortunately technological progress is not followed by moral, ethical and spiritual progress. Based on the information presented, it can be concluded that the basic problem in the